The Black Organic Intellectual Tradition and the Challenges of Educating and Developing Organic Intellectuals in the 21st Century. (1st July 2018) - Harris, Christopher
Abstract : By summarizing the legacy of the first and second wave Black working class organic intellectuals in North America in the 20th century, I will use this as a backdrop to discuss my efforts in the first decade of the 21st century to develop a third wave of organic intellectuals in the hip hop generation. I will offer a case study of the Freedom Cipher Program at the Black Action Defense Committee (BADC), and discuss the implications of this experience for organizing oppressed Black working class and underclass youth into organic intellectuals today in this age of neo-liberal capitalism and globalization. I hope this paper will contribute to the work of the revolutionary party-building Left, and youth movements concerned with organizing the hip hop generations of the 20th century (born 1965-1984) and 21st century (born 1985-2004) into a new socialist hegemonic project.